Archaeological reconnaissance in the Chicama Valley: Pyramids, configuration and use of space - Masías Leiva, Julio Rodolfo (2026)
The Chicama Valley, north of the city of Trujillo, is home to a wide dispersion of pyramidal structures on both banks of the river. The record obtained from surface archaeological surveys emphasized three criteria for identifying these structures: a) location and distribution; b) elevation and volume; and c) proximity to water resources. These criteria allow for the exploration of the reasons that led to the development of these pyramids and their location throughout the Chicama Valley